Infrasound induces coronary perivascular fibrosis in rats - Lousinha, Ana (2018)
BACKGROUND: Chronic exposure to industrial noise is known to affect biological systems, namely, by inducing fibrosis in the absence of inflammatory cells. In rat hearts exposed to this environmental hazard, we have previously found myocardial and perivascular fibrosis. The acoustic spectrum of industrial environments is particularly rich in high-intensity infrasound (<20 Hz), whose effects on the heart are unknown. We evaluated the morphological changes induced by IFS in rat coronaries in the presence and absence of dexamethasone. METHODS: Adult Wistar rats were divided into three groups: group A (GA)-IFS (<20 Hz, 120 dB)-exposed rats for 28 days treated with dexamethasone; group B (GB)-IFS-exposed rats; group C (GC)-age-matched controls. The midventricle was prepared for observation with an optical microscope using 100× magnification. Thirty-one arterial vessels were selected (GA 8, GB 10, GC 13). The vessel caliber, thickness of the wall, and perivascular dimensions were quantified using image J software. Mann-Whitney and Kruskal-Wallis tests were used to compare the groups for lumen-to-vessel wall (L/W) and vessel wall-to-perivascular tissue (W/P) ratios. RESULTS: IFS-exposed rats exhibited a prominent perivascular tissue. The median L/W and median W/P ratios were 0.54 and 0.48, 0.66 and 0.49, and 0.71 and 0.68, respectively, in GA, GB, and GC. The W/P ratio was significantly higher in GC compared with IFS-exposed animals (P=.001). The difference was significant between GC and GB (P=.008) but not between GC and GA. CONCLUSION: IFS induces coronary perivascular fibrosis that differs under treatment with corticosteroid.